2021
DOI: 10.1111/gcb.15559
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the potential distribution of bumble bees (Apidae:Bombus) in Mesoamerica under different climate change scenarios: Conservation implications

Abstract: Bumble bees are an ecologically and economically important group of pollinating insects worldwide. Global climate change is predicted to affect bumble bee ecology including habitat suitability and geographic distribution. Our study aims to estimate the impact of projected climate change on 18 Mesoamerican bumble bee species. We used ecological niche modeling (ENM) using current and future climate emissions scenarios (representative concentration pathway 4.5, 6.0, and 8.5) and models (CCSM4, HadGEM2‐AO, and MIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 101 publications
(156 reference statements)
1
21
1
1
Order By: Relevance
“…Much wildlife has shifted its geographic distribution toward higher elevations or latitudes [5,67,[77][78][79], and Chen et al's (2011) meta-analysis showed that the distribution of many species has recently shifted to higher elevations at a median rate of 11.0 m per decade [9]. Interestingly, we have not found such a shift to higher elevations, i.e., the distribution of Siberian ibex at different elevations remained unchanged under future climate scenarios.…”
Section: Discussioncontrasting
confidence: 57%
“…Much wildlife has shifted its geographic distribution toward higher elevations or latitudes [5,67,[77][78][79], and Chen et al's (2011) meta-analysis showed that the distribution of many species has recently shifted to higher elevations at a median rate of 11.0 m per decade [9]. Interestingly, we have not found such a shift to higher elevations, i.e., the distribution of Siberian ibex at different elevations remained unchanged under future climate scenarios.…”
Section: Discussioncontrasting
confidence: 57%
“…In recent years, studies in Chile have related climate variability to responses among pollinators and to the vigor and growth of woody species in native shrublands and forests (Fig. S1 available online as Supplemental Material;Fontúbel et al, 2018;Venegas-González et al, 2019;(Miranda et al, 2020), and similar trends were documented in productive systems elsewhere (Martínez-López et al, 2021;Phillips et al, 2018). In Chile, these studies have documented the effects of the recent megadrought, one of the most severe and prolonged droughts in Chile in the last millennium (Garreaud et al, 2020).…”
Section: Introductionmentioning
confidence: 66%
“…Changes in the number of beekeepers and hives may mask the effects of climate on honey production in many countries. Recently, Martínez-López et al (2021) documented a reduction in the bumblebee distribution in Mesoamerica related to climate change. Such warming trends particularly threaten specialist species and those with restricted distributions.…”
Section: Discussionmentioning
confidence: 99%
“…However, bumble bees are also among the few bees with documented significant changes in population vigor and geographical range shifts due to various anthropogenic factors, including climate change (Bommarco et al, 2012; Cameron et al, 2011; Colla & Packer, 2008; Martins & Melo, 2010; Soroye et al, 2020; Williams & Jepsen, 2014). In addition, studies under climate change scenarios using niche modeling approaches suggest significant reductions (up to 78%) in bumble bees' climatically suitable areas across North and South America, Europe, and East Asia (da Silva Krechemer & Marchioro, 2020; Françoso et al, 2019; Martínez‐López et al, 2021; Naeem et al, 2019). Furthermore, species richness of bumble bees is also expected to be reduced by changes in climatic conditions (Sirois‐Delisle & Kerr, 2018; Soroye et al, 2020).…”
Section: Introductionmentioning
confidence: 99%